FIXED POINT THEOREMS FOR MULTIVALUED MAPPINGS IN MODULAR B-METRIC SPACES - Hartono Hartono; Lusi Harini; Afifah Hayati; Syamsudin Mas'ud; Thesa Adi Saputra Yusri; Karyati Karyati; Fitriana Yuli Saptaningtyas (PATTIMURA UNIVERSITY, 2026)
This paper explores multivalued mappings in modular b-metric spaces, with particular emphasis on contraction-type mappings. It introduces the concept of a Hausdorff distance adapted to this setting and investigates fixed point theorems associated with these mappings. The existence of fixed points is established under the assumptions that the space is complete, the considered subset is closed, and the modular -metric satisfies the -condition. These results not only extend classical fixed point theory but also provide a theorem that guarantees the existence of solutions to integral equations, with potential applications in mathematical modeling.